PERBANDINGAN KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA ANTARA YANG MENGGUNAKAN PENILAIAN TUGAS DENGAN PENILAIAN PORTOFOLIO DALAM PEMBELAJARAN MATEMATIKA - yunus sunandar; Arif Muchyidin (EduMa: Mathematics education learning and teaching, 2016)
This study aimed to determine whether there are significant differences in mathematical thinking ability of students who use the assessment tasks with portfolio assessment. This research was conducted in class VIII B and VIII D SMPN 2 Cirebon. The sampling technique using random sampling techniques, with samples of 45 students for group assessment tasks (X1) and 45 students for portfolio valuation group (X2). The instrument used in this study are shaped test of 10 questions about the description. The results obtained by the mathematical creative thinking ability of students to use the assessment task has an average of 74.31 with a median and mode respectively 74.00 and 70.00. While the ability to think creatively mathematics students using portfolio assessment has an average of 79.69 with a median and mode respectively 80.00 and 82.00. Of hypothesis testing via t-test obtained tcount < ttable ie tcount = -4.557 , while ttable = 1.987, This case shows that there are no significant differences in mathematics creative thinking ability of students between the use of assessment tasks with portfolio assessment in mathematicsKeywords        :Assessment Task , Portfolio Assessment , and Creative Thinking Skills